BRCA and Pancreatic Cancer - Brennan, Gregory T; Relias, Valerie; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Germline mutations in BRCA genes have been associated with pancreatic cancer. Laboratory and clinical data suggest that patients with BRCA mutations may be more responsive to therapy consisting of conventional chemotherapy with a poly(ADP-ribose) polymerase inhibitor (PARPi). The most recent data from the 2013 American Society of Clinical Oncology (ASCO) Annual Meeting will be reviewed (Abstracts #11024 and #TPS4144). Image: Effect of PARP, BRCA and PARP inhibition on DNA replication.